Comparison the Analgesic Effects of Single Dose Administration of Tramadol or Piroxicam on Postoperative Pain after Cesarean Delivery - Amir Farshchi; Golbarg Ghiasi (Acta Medica Iranica, 2010)
"nA multimodal approach to postcesarean pain management may enhance analgesia and reduce side effects after surgery. We investigated postoperative pain in a double-blinded, randomized, single-dose comparison of the monoaminergic and µ-opioid agonist tramadol, 100 mg (Group T) and piroxicam 20 mg (Group P) given IM alone- single dose in 150 patients who had elective cesarean delivery. All patients were assessed at 0, 6, 12 and 24 hours post operation for pain degree (by Visual Analogue Score: VAS 1-10), nausea and vomiting. Pain degree was classified as: Painless: 0, Mild: 1-4, Moderate: 5-8, Severe: 9-10. There was no significant difference between the efficacy of tramadol and piroxicam injections (P>0.05). Pain intensity decreased markedly over time in both groups. Mean±SEM pain degrees were as follows: P=7.7±0.5, T=8.2±0.8 after 0 hours; P=5.4±0.6, T=6.1±0.5 after 6 hours; P=3.3±0.4, T=3.4±0.7 after 12 hours; P=1.1±0.4, T=1.3±0.5 after 24 hours of surgery. Side effects were similarly minimal with all treatments. It might be concluded that i.m. injections of 20 mg piroxicam (single dose therapy) could relieve postoperative pain after cesarean section as well as tramadol and it could reduce opioid analgesic requirements with less adverse side effects during the first postoperative 24 h.